2016
DOI: 10.29122/jtl.v13i1.1402
|View full text |Cite
|
Sign up to set email alerts
|

Aplikasi Metode Curve Number Untuk Mempresentasikan Hubungan Curah Hujan Dan Aliran Permukaan Di Das Ciliwung Hulu – Jawa Barat

Abstract: Aliran permukaan/limpasan (run off) merupakan salah satu variabel hidrologi yang sangat penting di dalam menunjang kegiatan pengembangan sumber daya air. Metode prediksi yang handal untuk menghitung jumlah dan laju limpasan yang berasal dari permukaan tanah dan bergerak menuju sungai di suatu DAS yang tidak dilengkapi alat ukur (ungaged watershed) adalah suatu pekerjaan yang sangat sulit dan memerlukanwaktu yang banyak. Penelitian ini dilakukan di DAS Ciliwung Hulu, yang merupakan daerah penting dalam kotribus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 2 publications
0
4
0
2
Order By: Relevance
“…The CN method is an empirical approach used to calculate direct runoff from rainfall occurrences, starting from the rainfall catchment area (watershed) [11]. The CN method estimates the runoff from the relationships among rainfall, ground cover, and hydrologic soil group (cover complex classification) [12]. The CN value may be estimated if the watershed's soil classification and ground cover are known.…”
Section: Analysis Of Curve Number (Cn)mentioning
confidence: 99%
“…The CN method is an empirical approach used to calculate direct runoff from rainfall occurrences, starting from the rainfall catchment area (watershed) [11]. The CN method estimates the runoff from the relationships among rainfall, ground cover, and hydrologic soil group (cover complex classification) [12]. The CN value may be estimated if the watershed's soil classification and ground cover are known.…”
Section: Analysis Of Curve Number (Cn)mentioning
confidence: 99%
“…Penelitian tentang nilai curve number sudah banyak dilakukan di DAS-DAS yang ada di Indonesia seperti DAS Ciliwung Hulu (Tikno dkk., 2012); DAS Garang Semarang (Sarminingsih dkk., 2019); DAS Temef di Nusa Tenggara Timur (Welkis dkk., 2020); dan DAS Benanain (Krisnayanti dkk;2021). Penelitian ini bertujuan untuk mengetahui nilai curve number di DAS Manikin.…”
Section: Latar Belakangunclassified
“…The primary role of remote sensing technology in runoff calculations is typically to generate input data and assist in calculating model coefficients and parameters. Experience has shown that various thematic information sources can be obtained through the interpretation of satellite imagery, including data related to land cover, soil, vegetation, and drainage patterns [2]. By combining the results of satellite image interpretation with traditional measurements, such as rainfall, temperature, and topography, new data for rainfall-runoff modeling is generated.…”
Section: Introductionmentioning
confidence: 99%